Stakeholders' Knowledge, Attitude, and Perceptions on the Control of Taenia solium in Kamuli and Hoima Districts, Uganda - Ngwili, Nicholas; Thomas, Lian; Githigia, Samuel; Johnson, Nancy; Wahome, Raphael; Roesel, Kristina (Frontiers in Veterinary Science, 2022)
Taenia (T.) solium is a zoonotic parasite causing three diseases: - Taeniasis and cysticercosis in humans and porcine cysticercosis in pigs. Although biomedically, the transmission of the parasite can be easily interrupted at six points along the life cycle, the contextual factors which may influence the adoption of these control strategies in Uganda remain unclear. This study assessed the stakeholders’ knowledge, attitudes and perceptions relating to the six control strategies for T. solium infections in Kamuli and Hoima districts, Uganda. A total of 22 focus group discussions (FGD) were conducted with pig farmers, community leaders, pig/pork traders, animal health assistants and human health assistants. In addition, nine key informant interviews were held with senior officials in the ministries of agriculture and health, and other relevant agencies at the district level. The results showed differential, limited and fragmented knowledge on T. solium infections among stakeholders. Pig farmers, community leaders and pig/pork traders had almost no knowledge and were often confused regarding the differences existing between T. solium and other gastro-intestinal infections in pigs and humans. Pig confinement, pit latrine construction, coverage, maintenance and sustained use are influenced by cultural, socio-economic, and physical/ environmental factors of study population and area. Proper sensitization programmes and health education interventions should target all, but with material appropriately focused to suit the different stakeholder’s categories. Reminders or nudges may be needed to ensure that increase in knowledge translates to changes in practice. Intervention programmes should also aim to overcome challenges created by the various contextual factors operating in the specific endemic areas.